Bark Water Storage Plays Key Role for Growth of Mediterranean Epiphytic Lichens - Porada, Philipp; Giordani, Paolo (Frontiers in Forests and Global Change, 2021)
Epiphytic lichens are a characteristic feature of many forests around the world, where they often cover large areas on stems and branches. Recently, it has been found that lichens may contribute substantially to carbon and nutrient uptake in forests. Moreover, they have a large influence on interception of rainfall at the global scale, which leads to a shift of the water balance towards evaporation and a cooling of near-surface air temperature. It is thus crucial to understand which environmental factors are relevant for their growth and survival, and which potential risks may result from climate change. Water supply is a key factor which controls active time and, consequently, the carbon balance of the epiphytes. However, it is largely unclear, to what extent different modes of water uptake, which include bark water, may affect active time and growth under varying environmental conditions. Quantitative estimates on the relevance of bark water storage and its interspecific variation are, however, missing. Here, we apply the process-based, dynamic non-vascular vegetation model LiBry to assess the relevance of bark water for epiphytic lichens. LiBry not only accounts for the main physiological processes of mosses and lichens, it also represents explicitly the diversity of the organisms, by simulating a large number of possible physiological strategies. We run the model for a site in Sardinia, where epiphytic lichens are abundant. Moreover, the Mediterranean region is of interest due to likely substantial effects of global warming on local epiphytes. For current climatic conditions, the LiBry model predicts net primary production (NPP) of 32 g C/m2/a per stem area and biomass of 48 g C/m2 for the study region. In a second run, where uptake of bark water is switched off in the model, estimated NPP is reduced by 21%. Moreover, the simulated number of surviving strategies, representing physiological diversity, decreases by 23%. This is accompanied by changes in the simulated community composition, where strategies which have a more compact thallus increase their share on the total cover. Hence, our model simulation suggests a substantial role of bark water for growth and morphology of epiphytic lichens in Sardinia.